PENGARUH MEDIA SOSIAL TERHADAP STRATEGI KOMUNIKASI DALAM NEGOSIASI BISNIS (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Effective marketing management is key to facing increasingly fierce competition and rapidly changing market1 dynamics. In this context, this study uses a descriptive-qualitative approach to explore marketing management techniques and promotional strategies that can increase sales and customer loyalty. The results of the study indicate that good service quality, including speed, friendliness, and responsiveness, significantly influences consumer satisfaction and loyalty. Furthermore, maintaining product quality that meets consumer expectations is also an important factor in building trust and loyalty. Competitive pricing, where consumers perceive they are getting value for their money, also contributes to repeat purchase decisions. Promotions conducted through KOLs have proven effective in building emotional connections between brands and consumers. KOLs with credibility and influence among their audiences can amplify promotional messages and increase product awareness. This study concludes that adaptive and innovative marketing strategies, especially those utilizing digital technology and social media, are crucial for MSMEs to create a competitive advantage in the modern marketplace. The results and recommendations from this study are expected to serve as guidelines for MSMEs in formulating more targeted and effective marketing strategies.